WIND ENERGY DEVELOPMENT AND POLICY IN INDIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
India is glorified with great renewable energy resources in general in that particularly wind energy. India stands at 4th position in the world for use of wind energy. Up to 2018, about 34605MW capacity wind power plants are installed .From last 10-20 years wind energy shows tremendous potential in capacity addition and generous production throughout the world. In case of India, wind energy is not only for production of power but also to fulfill the energy in a profitable way. This paper discusses the development opportunities and challenges associated with wind energy in the country. Also the present picture of wind power potential of India was compared with other leading countries in world.